Efforts to Increase Student Awareness of the Importance of Noble Morals with an Active Learning Approach at MI West Lampung - Dewi, Yumna (MANDAILING GLOBAL EDUKASIA, 2024)
Noble moral education is a fundamental aspect in the formation of students' character from an early age. This study aims to increase the awareness of grade 3 students of Madrasah Ibtidaiyah (MI) regarding the importance of noble morals through an active learning approach. The method used is a qualitative approach with learning strategies based on discussion, simulation, and role-playing. The results of the study indicate that active learning can improve the understanding and application of noble moral values ​​in everyday life. In addition, student involvement in the interactive learning process makes them more enthusiastic and motivated in developing positive attitudes, such as honesty, politeness, and empathy. Thus, an active learning approach can be an effective solution in instilling noble moral values ​​from an early age